2016
DOI: 10.3390/galaxies4040063
|View full text |Cite
|
Sign up to set email alerts
|

AP Librae: The Extended Jet as the Source of VHE Emission?

Abstract: Abstract:The LBL AP Librae has been detected in the TeV gamma-ray range, which is unexpected for this kind of blazar. The broad-band SED cannot be explained by a one-zone model, and especially fails in the TeV domain. An extended jet has been detected on arcsec scales both in radio and X-ray frequencies. The spectral index of the X-ray band indicates an inverse Compton origin. Using an IC/CMB model, the TeV emission can be successfully modeled as originating in the extended jet. Several arguments in favor of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…They attributed this to the gross non-simultaneity of the Fermi-LAT and X-ray observations (∼ 7 years) and the possible presence of an X-ray jet. However Sanchez et al (2015) confirmed these findings with quasi-simultaneous X-ray and Fermi /LAT observations (see also Zacharias & Wagner 2016).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…They attributed this to the gross non-simultaneity of the Fermi-LAT and X-ray observations (∼ 7 years) and the possible presence of an X-ray jet. However Sanchez et al (2015) confirmed these findings with quasi-simultaneous X-ray and Fermi /LAT observations (see also Zacharias & Wagner 2016).…”
Section: Introductionsupporting
confidence: 60%
“…Our aim in this study is to explain the very broad second component in AP Librae and in particular to test the clear predictions of the models invoking IC/CMB in the kpcscale jet for the TeV emission (e.g. Zacharias & Wagner 2016). These models predict a high level of infrared synchrotron emission from the jet, provided by the same electrons required to explain the TeV emission.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…From our highresolution VLA, ALMA, and HST imaging campaign we have been able to more accurately sample the synchrotron spectrum of the X-ray emitting jet (red data points and upper limit with phenomenological power-law+exponential cutoff model as a blue dashed curve). The infrared upper limit (in red) in particular rules out the IC/CMB model of [35], shown as cyan curves. In addition, a fit to the orange ALMA data points (orange-dashed) has been indicated, which is a blackbody at temperature 25 K, having typical size ∼ 100 pc.…”
Section: Figurementioning
confidence: 99%
“…Several efforts have been made to move beyond a simple SSC model and explain the TeV emission. Both [35] and [30] suggested that inverse Compton scattering off cosmic microwave background photons in the extended jet (the IC/CMB mechanism) could explain the high-energy LAT and H.E.S.S. emission, although the synchrotron emission of the large-scale jet was severely under-constrained in these works.…”
Section: Introductionmentioning
confidence: 99%